Gambaran Faktor-Faktor Perilaku Penyebab Kecelakaan Lalu Lintas Pengendara Sepeda Motor di SMAN 2 Gunung Putri Bogor Tahun 2019 - Alda Safira Utami; Herlina Herlina (STIKes Persada Husada Indonesia, 2020)
According to data from the Ministry of Transportation during 2016, there were 106,573 traffic accidents throughout Indonesia. A total of 73.9 percent involve motorcycles. Judging from the educational background, accident victims with high school education were 138,995 people in 2016. This study aims to describe the behavioral factors that cause motorcycle traffic accidents at SMAN 2 Gunung Putri Bogor. This study uses a qualitative design with a phenomenological approach. The type and research design used is descriptive. This research took place at SMAN 2 Gunung Putri, Bogor, Jalan Raya Kota Wisata no. 1, Ciangsana, Gunung Putri Bogor. Research focus on human factors, vehicle factors and environmental factors. The time of the research was carried out in April-May 2019. The sample in this qualitative study used purposive sampling of informants to select informants. In this study, the sample selected was 6 people, namely key informants. The data taken in the form of in-depth interviews, photo and video observations. Data analysis used a triangulation approach. Human factor: the average age of driving is 9 years old, they already have a driver's license when they are 17 years old and some take care of it through service bureaus. Vehicle factor: Students never experience brake failure because every 3 months they always carry out maintenance. On average, students change tires every 6 months. Students stated that the lights of student vehicles were automatically turned on during the day. Environmental factors: On the damaged roads there are still many students who overtake other vehicles. Students who pass through slippery roads, students drive at a high speed of 60 km. On the bend road students pass the road at a normal speed and some at high speed.